Study on the Effect of Mass Selection and Hybridization on Growth Performance of Chinese Pearl Oyster Pinctada martensii - Fan, Chao; Zhang, Xuekai; Tang, Liming; Zhang, Xingzhi; Li, Jinlong; Li, Yangchun; Li, Qiongzhen; Wang, Zhaoping (Frontiers in Marine Science, 2022)
The pearl oyster Pinctada martensii is an important species for sea pearl production in China. To explore the influence of the combination of mass selection and hybridization on growth performance of P. martensii, we established four selected groups and four control groups (each with two within-family crosses and two reciprocal hybrid crosses) using 1-year-old offspring of two families (Family A and Family B) from Beihai, Guangxi Province, China. Generally, the growth of the selected group was greater than that of the control group for both within-family crosses and reciprocal hybrid crosses. Shell length and width were affected by genotype, environmental factors, and the interaction between the two on Days 210 and 360. The shell widths of the four reciprocal hybrid crosses all showed heterosis on Day 360. The four within-family crosses showed a certain degree of inbreeding depression during the growth period. On Day 360, the three genetic parameters for shell width of the selected group of ♀ Family B and ♂ Family A were the largest, with values of 0.70, 1.17, and 0.06 for realized heritability, standard response to selection, and current genetic gain, respectively. Overall, the growth performance of ♀ Family B × ♂ Family A in the selected group was the best. Therefore, the combination of mass selection and hybridization could be an effective way to improve the growth performance of P. martensii.